अग्नि महाकाव्यमा दलित सन्दर्भ - Rijal, Puskar Nath (Haimaprabha, 2025)
The present article explores the Dalit references found in the Agni Mahakavya composed by the poet Nawaraj Lamsal. For this, the Dalit aesthetics and Marxist perspective that have developed in recent times in literature have been used as the theoretical basis. The Dalit community has been suffering for centuries due to the Hindu Brahmanical structure of Nepali society. In the Agni Mahakavya, the Hindu caste system has placed Dalits in the lower and untouchable class, despite the participation of Dalits in every national issue. They are not valued, the life of the people of the Dalit community is very difficult. The Dalit community has to migrate due to social insecurity, and they have never been in the eyes of the state. In addition, the epic seriously raises the issues of Dalit cultural prestige, Dalit women and children, and presents a humanistic perspective. The essence of the Agni Mahakavya is to establish characters like Thule and Chhelangi of the Dalit community who make a living by running arana as heroes, and desire Dalit rights and liberation. Written with the bitter reality of the contribution of the working class, the poor, and the Dalits, who served as assistants to the ruling class in various periods of history, Agni is a poem that raises the Dalit issue in a very powerful way. Agni stands as an excellent epic poem in terms of Dalit context and Marxist aesthetics. It raises the voice of protection of the rights of the Dalit community, who have been living a precarious life. They are not recognized by their own country because of the dominance of the Brahmanical thinking.